A reflection of organizational citizenship behaviors in the performance of employees A prospective study of a sample of the teaching staff working in the Degla University College - حميد, ريم مهند (Journal of Economics and Administrative Sciences, 2016)
Abstract         This research aims to identify the relationship and the impact of the behavior of organizational citizenship in the performance of employees, as practiced behaviors organizational citizenship substantial role in achieving the objectives of both the organization and its staff at the same time, so it affects a large extent on the characteristics and performance of individuals employees and thus influence the success of the organization as a whole, problem of the research has indicated that there is a clear failure in the study of the impact of the behavior of organizational citizenship in the performance of employees, was chosen as the education sector as a field of application, as chosen number of teaching staff working in the Tigris University College as a sample for research and by (82), The resolution was adopted as a tool to obtain data Find which had been prepared on the basis of a number of measures ready, and use the program Statistical Ready (SPSS) in introducing and analyzing research data is the most important statistical tools used in the analysis: "The percentage of recurrence, and the arithmetic mean, and standard deviation and coefficient of variation, and the correlation coefficient (Spearman), and linear regression simple ", has resulted in the statistical tools for a number of results confirmed most of an association and the impact of the relationship of significance between organizational communication and promote behaviors organizational citizenship and these results are consistent with the basic premises from which the search, and the researcher recommended the need to increase the interest of the surveyed Organization studying how to activate the role of organizational citizenship behaviors and use them in strengthening the performance of their employees.